Cell-penetrating peptides with intracellular organelle targeting. (1st February 2017) - Cerrato, Carmine Pasquale; Künnapuu, Kadri; Langel, Ülo
ABSTRACT: Introduction : One of the major limiting steps in order to have an effective drug is the passage through one or more cell membranes to reach its site of action. To reach the action-site, the specific macromolecules are required to be delivered specifically to the cell compartment/organelle in their (pre)active form. Areas covered : In this review, we will discuss cell-penetrating peptides (CPPs) developed in the last decade to transport small RNA/DNA, plasmids, antibodies, and nanoparticles into specific sites of the cell. The article describes CPPs in complex with cargo molecules that target specific intracellular organelles and their potential for pharmacological or clinical use. Expert opinion : Organelle targeting is the ultimate goal to ensure selective delivery to the site of action in the cells. CPP technologies represent an important strategy to address drug delivery to specific intracellular compartments by covalent conjugation to targeting sequences, potentially enabling strategies to combat genomic diseases as well as infections, cancer, neurodegenerative and hereditary diseases. They have proven to be successful in delivering various therapeutic agents into cells however, further in vivo experiments and clinical trials are required to demonstrate the efficacy of this technology.